COMMUNICATION PRIVACY MANAGEMENT AMONG GEN-Z INFLUENCERS: EXPLORING THE INSTAGRAM NGL FEATURE AND ILLUSION OF SOCIAL CLOSENESS - Dessy Mutiara Cipta; Silvanus Alvin (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This research discusses the phenomenon of using the NGL Link or Not Gonna Lie feature on Instagram, which allows users to answer anonymous questions. It highlights the Communication Privacy Management (CPM) theory and its relevance to understanding how individuals manage their personal information. The research aims to explore the motivations of micro-influencers, specifically from Generation Z, in using the NGL Link feature and how they manage communication privacy on their Instagram main accounts. The methods used in this qualitative research include interviews and data documentation. The results and discussion section presents the findings from interviews with four micro-influencers, highlighting their different approaches to communication privacy management and motivations for using the NGL Link feature. One interesting finding is the existence of an illusion of closeness between micro-influencers and their followers on social media.